Pengembangan Video Motivasi pada Materi Ikatan Kimia - Lalang, Arvinda Ceniorita (JURNAL EKSAKTA PENDIDIKAN (JEP), 2024)
This ethnoscience motivational video was created utilizing the Microsoft Office PowerPoint 2021 application. This research uses the flow or steps of the design model from Borg & Gall as modified according to its needs. In this research, there are 5 main steps, such as preliminary studies, product design, validation, product trials, and final product results dissemination. The questionnaire was approved by instrument experts and declared feasible for validation and product trials. Product validation was carried out by three material experts and media experts each. The calculation results of each overall ideal percentage were 98% for learning material experts and 96.47% for media experts. The calculation results show that the motivational video is suitable for testing with an excellent category. Once the product was confirmed, class X students at various high schools in East Kupang conducted product trials in small and large groups. The evaluation of this product through a small group test involving eight students from a single high school yielded excellent results with an impressive 90% score, while the large group test with 32 students from three high schools achieved outstanding results with an impressive 96.25% score. Based on the results of product validation assessments and product trials of ethnoscience motivational videos on chemical bonding material, it is feasible to use them as media in early learning activities